Examining the relationship between decoding and comprehension in L2 listening. (December 2019) - Leonard, Karen Ruth
Abstract: In L2 listening research, there is debate over the roles of bottom-up and top-down processing in comprehension. However, little previous research has examined the relationship between listeners' ability to aurally decode individual words (an aspect of bottom-up processing) and their overall comprehension of listening texts (believed to be the result of both bottom-up and top-down processes). Additionally, the extent to which L2 listeners use context to compensate for aural decoding difficulties is unclear. In this study, 25 intermediate to advanced learners of Spanish (L1 English) listened to excerpts of three stories in Spanish. They completed a recall protocol in their L1 and a transcription task in the L2 for each story. Results indicate that good comprehension (defined as a score of ≥70% on the recall protocol) was sometimes achieved when participants correctly decoded as few as 73.5% of the words in the story, but only scores of ≥93.0% on the transcription task were consistently associated with good comprehension, which provides preliminary evidence suggesting a strong relationship between accurate aural decoding and good comprehension. Additionally, only 16.6% of aural decoding errors were semantically appropriate to the context, which suggests a limited role for context in participants' decoding of the input.